Physiological tissue losses of feedlot cattle transported for slaughter in South Africa - Webb, E.C. (Edward Cottington) (University of Pretoria, 2023)
Dissertation (MScAgric (Animal Science Production Physiology and Product Quality))--University of Pretoria, 2022.